1998
DOI: 10.1002/(sici)1521-4141(199801)28:01<47::aid-immu47>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I expression protects target cells from lysis by Ly49-deficient fetal NK cells

Abstract: Using appropriate conditions natural killer (NK) cells can be cultured from the liver and thymus of day 14 fetal mice. These fetal NK cells are phenotypically and functionally indistinguishable from adult NK cells with the exception that they lack measurable expression of all of the Ly49 molecules that can currently be detected with antibodies. Despite this, they preferentially kill tumor cells and blast cells deficient in the expression of major histocompatibility complex class I molecules, although the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…It has been previously described that Ly49 + splenic NK cells are absent at birth and gradually appear during the first 6-8 weeks of life [16,17]. Surprisingly, Ly49 -NK cells from fetal and 5-day-old mice have been shown to selectively kill MHC class I-deficient cells [16,18,19]. Additionally, we have observed high killing of YAC-1 cells by newborn-derived NK effector cells (unpublished observations).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been previously described that Ly49 + splenic NK cells are absent at birth and gradually appear during the first 6-8 weeks of life [16,17]. Surprisingly, Ly49 -NK cells from fetal and 5-day-old mice have been shown to selectively kill MHC class I-deficient cells [16,18,19]. Additionally, we have observed high killing of YAC-1 cells by newborn-derived NK effector cells (unpublished observations).…”
Section: Discussionsupporting
confidence: 59%
“…A gradual increase of Ly49 + cells among the NK1.1 + population is observed during the first weeks of age and adult levels are reached within approximately 20 days after birth ( [16,17], and the present study). Expression of CD94 and Ly49E transcripts have been detected early in NK cell ontogeny [18,19], but the expression of these molecules has not been characterized in detail. The relationship between the establishment of the NK cell receptor repertoire and the functional maturation of NK cells is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that expression of these receptors is limited to more immature NK cells, which may persist in the study carried out here due to the in vitro culture conditions utilized. In support of expression of Ly49E by immature NK cells, Toomey et al [22] found that, although fetal NK cell lines generally lacked detectable levels of most Ly49 molecules, they expressed high levels of mRNA for Ly49E but not other Ly49.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, some clones and lines that develop from fetal progenitors contain small numbers of cells that express Ly49C/I or G, suggesting that the Ly49 genes in these cells are in a potentially expressible state [2]. Secondly, abundant levels of mRNA for Ly49E have been found in these cells [5]. We report here that the majority of NK cells that develop in vitro from fetal thymus progenitors in fact express high levels of previously uncharacterized Ly49 molecules, most likely Ly49E, on their surfaces.…”
Section: Introductionmentioning
confidence: 99%